Thermally stable and flame retardant polymer nanocomposites - Mittal, Vikas (Cambridge University Press, 2011)
"Polymer nanocomposites have revolutionised material performance, most notably in the plastics, automotive and aerospace industries. However, in order to be commercially viable, many of these materials must withstand high temperatures. In this book, leaders in the field outline the mechanisms behind the generation of suitable polymer systems, pulling together recent research to provide a unified and up-to-date assessment of recent technological advancements. The text is divided into two clear sections, introducing the reader to the two most important requirements for this material type: thermal stability and flame retardancy. Special attention is paid to practical examples, walking the reader through the numerous commercial applications of thermally stable and flame retardant nanocomposites. With a strong focus on placing theory within commercial context, this unique volume will appeal to practitioners as well as researchers"-- Provided by publisher.
Keywords: Fire resistant polymers.; Nanocomposites (Materials); elektronické knihy; electronic books